The Relationship Between Post-Of-Mothers' Knowledge and Umbilical Cord Care In The Working Area Of Bies Public Health Center, Central Aceh Regency - Nurlaely HS; Rahmah; Lia Muslima; Helina Syafutri (Jurnal Maternitas Kebidanan, 2026)
Umbilical cord care is a key aspect of neonatal care, particularly during the first two weeks of life. Umbilical cord care involves treating and tying the umbilical cord, physically separating the mother from the baby. The cord is then cared for in a clean state to prevent infection. Objective: This study aimed to determine the relationship between postpartum mothers knowledge and umbilical cord care in the Bies Community Health Center working area in Central Aceh Regency. Method: This study was descriptive and analytical. Total sampling was used. Respondents were 22 postpartum mothers. The research instrument was a questionnaire consisting of 20 questions about personal matters and respondents' knowledge. Data were analyzed statistically using the Fisher's exact test using SPSS. Results: Statistical analysis showed a relationship between postpartum mothers knowledge and umbilical cord care (P = 0.001). Conclusion: Umbilical cord care is crucial for preventing infection. This can reduce infant mortality. Therefore, further education on umbilical cord care in health services is needed in the future.